2021
DOI: 10.1073/pnas.2020230118
|View full text |Cite
|
Sign up to set email alerts
|

An interpreted atlas of biosynthetic gene clusters from 1,000 fungal genomes

Abstract: Fungi are prolific producers of natural products, compounds which have had a large societal impact as pharmaceuticals, mycotoxins, and agrochemicals. Despite the availability of over 1,000 fungal genomes and several decades of compound discovery efforts from fungi, the biosynthetic gene clusters (BGCs) encoded by these genomes and the associated chemical space have yet to be analyzed systematically. Here, we provide detailed annotation and analyses of fungal biosynthetic and chemical space to enable genome min… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 69 publications
3
110
0
Order By: Relevance
“…To gain insight into a possible PeXanC binding site and to gain perspective on the evolution of XanC in fungi, we identified homologous xan and cit BGCs using multigene BLASTN and BLASTP (see Materials and Methods for details). Because recent analysis of gene cluster families (GCFs) across all fungi ( 39 ) has suggested that the cit GCF is narrowly distributed within Eurotiales , we limited our search to the NCBI genome database within this group. In order to avoid possibly pseudogenized cluster variants that might confound our assessment of the relationship between xanC sequences and the presence of the xan and cit BGCs, we selected 16 species (11 Penicillium spp.…”
Section: Resultsmentioning
confidence: 99%
“…To gain insight into a possible PeXanC binding site and to gain perspective on the evolution of XanC in fungi, we identified homologous xan and cit BGCs using multigene BLASTN and BLASTP (see Materials and Methods for details). Because recent analysis of gene cluster families (GCFs) across all fungi ( 39 ) has suggested that the cit GCF is narrowly distributed within Eurotiales , we limited our search to the NCBI genome database within this group. In order to avoid possibly pseudogenized cluster variants that might confound our assessment of the relationship between xanC sequences and the presence of the xan and cit BGCs, we selected 16 species (11 Penicillium spp.…”
Section: Resultsmentioning
confidence: 99%
“…SM = secondary metabolite, PSTF = pathway specific transcription factor, NRPS = nonribosomal peptide synthetase, HR-PKS = highly reducing polyketide synthase, NR-PKS = non-reducing polyketide synthase, TC = terpene cyclase. 1 No conserved domain means PSTF without conserved domain. 2 "x + x(+x)" means biosynthesis genes are not all located in a single cluster but in at least two chromosomal sites.…”
Section: Aspergillus Fumigatusmentioning
confidence: 99%
“…Secondary metabolites (SMs) in fungi, also known as natural products, are present and synthesized in ecologically diverse species [1]. In fungi, SMs can provide self-protection and act as mediators for communication with other organisms or as virulence factors during pathogenic interactions with plants and animals [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the COCONUT database has recently been leveraged to create a resource (called LOTUS) directly linking natural product chemical structures to freely available articles describing the characterization and biological evaluation of the compounds. 8 In another recent report, the Natural Products Atlas was queried by Robey et al 9 to collect data from 15 213 fungal metabolites. These compounds were organized into molecular families and used to annotate the fungal gene clusters from 1000 fungal genomes.…”
Section: Developments In Storing and Accessing Natural Product Chemical Structuresmentioning
confidence: 99%